Effects of Rhythmic Transcranial Magnetic Stimulation in the Alpha-Band on Visual Perception Depend on Deviation From Alpha-Peak Frequency: Faster Relative Transcranial Magnetic Stimulation Alpha-Pace Improves Performance - Coldea, Andra; Veniero, Domenica; Morand, Stephanie; Trajkovic, Jelena; Romei, Vincenzo; Harvey, Monika; Thut, Gregor (Frontiers in Neuroscience, 2022)
Alpha-band oscillatory activity over occipito-parietal areas is involved in shaping perceptual and cognitive processes, whereby a growing body of electroencephalographic (EEG) evidence has indicated that pre-stimulus alpha-band amplitude relates to the subjective perceptual experience, but not to objective measures of visual task performance (discrimination accuracy). The primary aim of the present transcranial magnetic stimulation (TMS) study was to investigate whether causality can be established for this relationship using rhythmic (alpha-band) TMS entrainment protocols. It was anticipated that pre-stimulus 10Hz-TMS will induce changes in subjective awareness ratings but not accuracy in the visual hemifield contralateral to TMS. To test this, we administered 10Hz-TMS over the right intraparietal sulcus prior to visual stimulus presentation in 17 participants, while measuring their objective performance and subjective awareness in a visual discrimination task. Arrhythmic and 10Hz sham-TMS served as control conditions (within-participant design). Resting EEG was used to record individual alpha frequency (IAF). A study conducted in parallel to ours with a similar design reported after we completed data collection (Di Gregorio et al., 2022) informed further tests for a causal relationship between pre-stimulus alpha-frequency and discrimination accuracy. We addressed this secondary aim by performing a regression analysis between rhythmic-TMS alpha-pace relative to IAF and performance measures. Our results revealed that contrary to our primary expectation, pre-stimulus 10Hz-TMS did not affect subjective measures of performance, nor accuracy, relative to control-TMS. This null-result is in accord with findings of Di Gregorio et al. (2022) who showed that for influencing subjective measures of performance, alpha-TMS needs to be applied post-stimulus. In addition, our secondary analysis showed that IAF was positively correlated with task accuracy across participants, and that 10Hz-TMS effects on accuracy - but not awareness ratings – depended on IAF: The slower (or faster) IAF was relative to the fixed 10Hz TMS frequency, the stronger the TMS-induced performance improvement (or worsening), indicating that 10Hz-TMS produced a gain (or a loss) in individual performance, directly depending on TMS pace relative to IAF. In support of recent reports, this is evidence for alpha-frequency playing a causal role in perceptual sensitivity likely through regulating the speed of sensory sampling.